(untitled) (CAHIERS MAGELLANES-NS, 2024)
The backbone of India's economy is its small and medium-sized enterprises (SMEs), which encounter numerous obstacles on the road to long-term viability. There may be several factors as to why small-scale industries fail due to lack of insufficient capital, competition, technology, human resources, natural disasters, and globalization. If small firms want to stay in business and compete, they need to focus on improving employee performance by making them more invested in their work and hence more productive. There is a dearth of data from small-scale enterprises that explains the features of performance management systems that engage workers. However, it is unclear that how small-scale industries will fare in the long run. Management of small-scale industries' overall performance and employee engagement were two separate concepts that this study aimed to merge. Similar to how neither concept is often thought of in conjunction with the other, researchers and practitioners are presently interested in both. The purpose of this research was to determine how significant the two concepts are for small scale industries. The basis of this study was a correlational analysis. Data was collected and analysed from 413 small-scale industry employees in the cities of Western Uttar Pradesh through survey research. In general, the study's results imply that small industries with performance management integrated into their business processes see higher levels of employee engagement. The results indicated that small business productivity and organizational success are aided by overall performance management and overall staff engagement.\